Analysis Characteristic of Province Travelling Intercity of AKDP Makassar-Parepare Route, South Sulawesi - St. Maryam Hafram; Herman Parung; Tri Harianto; Muh. Isran Ramli (IPTEK Journal of Proceedings Series, 2014)
Intercity Transportation is a kind of transportation that connects one city to other cities that are still located in one provincial administrative region or province intercity, as well as located in the other provinces. province intercity service works in one route network and the road infrastructure as contained in the regulation route reguirement. The type and amount of Goods Mode In this study are Damri Bus, Minibus, BMA, and the types of MPU vehicles conprises of Panther, Kijang, Avanza etc. The purpose of this study is to analyse the travelling Charakteristics of AKDP that comprises of passenger and operator, travelling expense of AKDP, which is covering of passenger expense and operational vehicles cost (BOK) of Makassar-Pare pare route. The survey of data collection for passengers was done at the locations of departure and transit of province intercity transportation that is in Daya regional terminal and unofficial terminals in a number of departure points along Perintis Kemerdekaan Street up to the borders of Makassar, the base of public transportation of province intercity base located in Makassar suburban areas and the stopovers province intercity Barru and Parepare.